Sprememba cene v gradbeni pogodbi - Juhart, Miha (Pravni letopis, 2022)
The author discusses the system of adjusting the price for construction works in construction contracts. The Obligation Code prescribes the mechanism of adjusting as an obligatory rule even in the case that the parties conclude the contract with fix price. Beside the Obligation Code also the Special Rules for Construction Contracts issued by the Slovenian Chamber of Commerce regulate the price adjustment. This regulation is slightly different and more favorable for the constructor. Author discusses many different problems concerning the application of the special rules. The change in price is caused by price changes in the market for materials and labor. When the contract includes the clause on fix price, the constructor can demand the price difference when the changes are over 10%. Special attention is put on contracts concluded in public procurement procedure.
Keywords: gradbene pogodbe; gradbeno pravo; javno naročanje; pogodbe; pogodbeno pravo; Posebne gradbene uzance; sprememba cene; spremenjene okoliščine